Penerapan Metode Bermain Peran Dalam Meningkatkan Ketrampilan Bahasa Inggris Pada Anak Usia Dini - Erni Andriya Ningsih; Bambang Harmanto; Muhammad Azam Muttaqin (Universitas Muhammadiyah Metro, 2024)
The purpose of this study is to find out how the role play method can be applied to improve the English language skills of young children in Kindergarten Group B of Bakalani Village, Purwantoro District, Wonogiri Regency. This study was conducted in Purwantoro District Bakalan Village Kindergarten, the number of subjects was 19 children, 10 of which were 5-6 years old boys and 9 were girls. This research method uses classroom action research. This study was conducted in 3 cycles and each cycle was conducted in two meetings. The research data collection techniques are observation and speaking skills tests. Meanwhile, the data analysis technique used in this study is a descriptive statistical analysis method that uses percentages. Based on research findings and data analysis, the role-playing method can improve students' #039; English language skills. This can be seen in the survey on the classroom performance of the students in the first session and#039; The knowledge of the English language is only 16% or still classified as very poor. After that, continuing in cycle II, students and#039; English proficiency increased to 44 percent or was still classified as poor. Then in cycle III, the increase was 78% or classified as good.